Resolving urban Canada goose problems in Puget Sound, Washington: A coalition-based approach - Woodruff, Roger A.; Sheler, Jim; McAllister, Kelly; Harris, Donald M.; Linnell, Michael A.; Price, Keel I. (eScholarship, University of California, 2004)
Recent decades have seen dramatic increases in resident populations of urban western Canada geese throughout the United States, including locations in the Puget Sound in western Washington. By 1987, populations of urban Canada geese grew to problematic levels in the greater Seattle area, and caused such extensive damage that the Seattle Metropolitan Area Waterfowl Management Committee (Seattle Metropolitan WMC) was formed. The Seattle Metropolitan WMC was comprised of 15 representatives from cities and jurisdictions in the greater area, the U.S. Department of Agriculture Wildlife Services, and the University of Washington. The Seattle Metropolitan WMC worked with state and federal wildlife agencies, advocate groups, and the public to identify their concerns, determine the extent of the problem, and formulate management options. Non-lethal management options, including relocation, were implemented in 1989. Egg-oiling was initiated in 1993. Relocation efforts were phased out after 1995, and the first substantial lethal removal was begun in 2000. Other management actions taken by the Seattle Metropolitan WMC included harassment, exclusion, repellents, habitat modifications, and public education. In 1998, escalating urban Canada goose problems in another area of Puget Sound precipitated the formation of a second committee, south of Seattle, involving Thurston County and the cities of Olympia, Lacey, and Tumwater. Using a slightly different approach than the Seattle Metropolitan WMC, management officials opted to hold a public meeting to solicit input and participation from individuals, groups, and agencies. Attendees were encouraged to serve on a steering committee which, when formed, included city and county officials, park managers, state and federal wildlife biologists, hunters, advocate groups, and citizens. Over the next 18 months, the committee identified problem areas, considered public concerns, reviewed management options, and utilized volunteers to count geese. From these efforts, a Resident Canada Goose Management Plan was developed. The plan, which was implemented in 2000, identified population and program objectives utilizing a full range of management options. The Seattle and Thurston County programs each were successful in reducing urban Canada goose problems. In Thurston County, a fully integrated approach including population reduction through lethal control was implemented in the first year. An immediate reduction in goose problems was evident, and the plan objectives were achieved within 4 years. In the Seattle area, goose damage problems were not substantially reduced until after the implementation of lethal removal in 2000. By 2003, the fourth season involving lethal removal, the number of urban geese and their associated damage had been reduced by approximately 60%. In both locations, the need for lethal removal declined during successive years of the program. Animal rights groups were vocal and took action to prevent lethal removal, but public demands for removal grew during the late 1990s as goose problems worsened. Although controversial at first, public and media support grew as facts came to light and Canada goose conflicts were reduced.